Overview of the pond slider Trachemys scripta (Thunberg in Schoepff, 1792) (Testudines: Emydidae) records in Montenegro - Vuk Iković; Jelena Popović; Slađana Gvozdenović-Nikolić (Natura Sloveniae)
The Pond Slider is one of the 100 world's most invasive alien species, widely introduced to Europe and all over the world. The number of specimens recorded in nature is increasing in the Balkans, including Montenegro. In this paper, we present literature and new findings of pond sliders in this country. So far, 10 known localities have been identified, most of them in the Mediterranean biogeographical region. Records are from different aquatic ecosystems, including lakes, ponds, rivers and streams. Locality Mrke-Blizna is identified as a potential breeding site, as numerous specimens are present here including hatchlings.